Multimedia - Vaughan, Tay
INTERNATIONAL EDITION, brand New, International/Global Edition, NOT LOOSE LEAF VERSION,NO SOLUTION MANUAL, NO CD, NO ACCESS CARD, Soft Cover/ Paper Back written in English, Different ISBN and Cover Image from US Edition; Sometimes, the title is different from US Edition, and the exercises and homework problem are in different orders or maybe completely different than the US edition, Please email us for confirmation. Some books may show some word such as Not for Sale or Restricted in US on the cover page